Neural predictors of motor control and impact of visuo‐proprioceptive information in youth. Issue 11 (7th August 2017) - Corporaal, Sharissa H.A.; Gooijers, Jolien; Chalavi, Sima; Cheval, Boris; Swinnen, Stephan P.; Boisgontier, Matthieu P.
Abstract: For successful motor control, the central nervous system is required to combine information from the environment and the current body state, which is provided by vision and proprioception respectively. We investigated the relative contribution of visual and proprioceptive information to upper limb motor control and the extent to which structural brain measures predict this performance in youth ( n  = 40; age range 9–18 years). Participants performed a manual tracking task, adopting in‐phase and anti‐phase coordination modes. Results showed that, in contrast to older participants, younger participants performed the task with lower accuracy in general and poorer performance in anti‐phase than in‐phase modes. However, a proprioceptive advantage was found at all ages, that is, tracking accuracy was higher when proprioceptive information was available during both in‐ and anti‐phase modes at all ages. The microstructural organization of interhemispheric connections between homologous dorsolateral prefrontal cortices, and the cortical thickness of the primary motor cortex were associated with sensory‐specific accuracy of tracking performance. Overall, the findings suggest that manual tracking performance in youth does not only rely on brain regions involved in sensorimotor processing, but also on prefrontal regions involved in attention and working memory. Hum Brain Mapp 38:5628–5647, 2017 . ©2017 Wiley Periodicals, Inc.